Perlindungan Hukum Kepada Pemilik Merek PS Glow Berdasarkan Putusan Pengadilan Niaga Surabaya Nomor 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Sby - Nurhayati Nurhayati; Teng Berlianty; Theresia Nolda Agnes Narwadan (PATTIMURA Law Study Review, 2023)
ABSTRACT: Disputes over the use of the Ms Glow trademark, which has similarities in principle to the Ps Glow trademark, so the authors researched to analyze and understand the decision of the Surabaya Commercial Court Number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Sby in providing legal protection to the brand owner and aims to analyze and understand the legal remedies that can be taken by the owner of the Ps Glow brand against a partially granted decision. This research is normative juridical research conducted using statutory approaches, conceptual approaches, and case approaches. Then the sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The legal material collection technique used was the collection of legal literature which was then analyzed using qualitative methods. The results of this study indicate that the Surabaya Commercial Court Decision Number 2/Pdt.Sus.HKI/Merek/2022/PN Niaga Sby has provided legal protection to brand owners by giving recognition to brand owners in the form of exclusive rights or the sole right to trademarks. Legal actions that can be taken by the owner of the Ps Glow brand against the decision which was partially granted was by cassation. This refers to the Trademark Law which regulates legal remedies for trademark cancellation disputes directly to the cassation level because in resolving trademark disputes there are no appeals but direct appeals